2009
DOI: 10.4317/medoral.15.e65
|View full text |Cite
|
Sign up to set email alerts
|

Dental implants in patients treated with oral Bisphosphonates: A bibliographic review

Abstract: Bisphosphonates inhibit bone resorption and are used to treat a range of pathologies, including Paget disease, osteoporosis, multiple myeloma and metastases associated with breast or prostate cancer. At present, there is no effective treatment for bisphosphonate induced osteonecrosis, so prevention is extremely important. Since quality of life deteriorates for those suffering osteonecrosis, maximum precautions should be taken with patients at risk, and especially whenever oral surgery, including dental implant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 13 publications
0
15
0
7
Order By: Relevance
“…(13) O teste Telopeptídeo carboxiterminal do coláge-no tipo I (CTX) é recomendado para avaliar o risco de osteonecrose naqueles pacientes utilizando bisfosfonatos por mais de três anos, sendo ideais os níveis maiores do que 150 pg / mL para a realização de qualquer tipo de operação com o mínimo risco e sem a necessidade de suspender medicação e, quando estes forem inferiores a 150 pg / mL, a medicação deve parar por um período de entre quatro e seis meses ou outra opção de tratamento protéti-co deve ser preferível. (13) Nos estudos presentes na literatura, relata-se a necessidade de mais evidên-cias científicas, a fim de validar o teste CTX como uma técnica para a prevenção da osteonecrose e, por conseguinte, a introdução ou não introdução deste teste sobre os protocolos pré-cirúrgicos; (14) se o mesmo é válido para avaliação do risco (12) e cautela sobre a capacidade preditiva da CTX e seu uso detalhado no consentimento informado. (15) Em um estudo no Sul da Austrália foram encontradas falhas num total de sete implantes em pacientes recebendo tratamento com BFs orais com integração ideal, sendo diagnosticado ONMB após um intervalo médio de 20,9 meses.…”
Section: Resultsunclassified
“…(13) O teste Telopeptídeo carboxiterminal do coláge-no tipo I (CTX) é recomendado para avaliar o risco de osteonecrose naqueles pacientes utilizando bisfosfonatos por mais de três anos, sendo ideais os níveis maiores do que 150 pg / mL para a realização de qualquer tipo de operação com o mínimo risco e sem a necessidade de suspender medicação e, quando estes forem inferiores a 150 pg / mL, a medicação deve parar por um período de entre quatro e seis meses ou outra opção de tratamento protéti-co deve ser preferível. (13) Nos estudos presentes na literatura, relata-se a necessidade de mais evidên-cias científicas, a fim de validar o teste CTX como uma técnica para a prevenção da osteonecrose e, por conseguinte, a introdução ou não introdução deste teste sobre os protocolos pré-cirúrgicos; (14) se o mesmo é válido para avaliação do risco (12) e cautela sobre a capacidade preditiva da CTX e seu uso detalhado no consentimento informado. (15) Em um estudo no Sul da Austrália foram encontradas falhas num total de sete implantes em pacientes recebendo tratamento com BFs orais com integração ideal, sendo diagnosticado ONMB após um intervalo médio de 20,9 meses.…”
Section: Resultsunclassified
“…Review of the current literature reflects a limited, but growing, knowledge of the relative risks to dental implant treatment in patients receiving bisphosphonate medication [139,[170][171][172][173][174][175][176][177][178][179]. There have been several case reports and series that have evaluated implant failures in patients receiving intravenous bisphosphonate therapy [180], while other retrospective studies have indicated that there may be risks of osteopathology developing in patients receiving oral bisphosphonates and dental implant treatment [10][11][12][13][14].…”
Section: Bisphosphonates and Dental Implantsmentioning
confidence: 99%
“…Oral BFs are used to treat osteoporosis, Paget's disease and osteogenesis imperfecta. Osteonecrosis of the jaw following oral surgery, including implant placement, has been described in patients taking BFs (27), and tooth extractions are the main cause (28)(29)(30). Few articles in the reviewed literature (26,31,32) report cases of osteonecrosis associated with BFs after implant placement which may be due to the low frequency of implant placement in patients undergoing BF treatment (32).…”
Section: Peri-implant Painmentioning
confidence: 99%